The Influence of Connected Mathematics Project (CMP) Learning Models on Student’s Mathematical Communication Ability in View of Self Esteem - Rizkya Elsa Armadhani; Yesi Franita; Aprilia Nurul Chasanah (Pendidikan Matematika STKIP Kusuma Negara, 2023)
This study examines the effectiveness of the Connected Mathematics Project (CMP) learning model in improving students' mathematical communication skills at MA Madarijul Huda Pati. Because of 46.15% of students demonstrating very low skills and 23.07% falling into the low category, the study aims to: (1) analyze the impact of CMP on mathematical communication skills, (2) compare skills among students with high, moderate, and low self esteem, and (3) explore the interaction between CMP and self esteem. Employing a quantitative quasi-experimental approach, the study involves class XI students selected through cluster random sampling. Results indicate a significant improvement in mathematical communication skills through CMP. Students with high self esteem outperform those with moderate self esteem, while those with moderate self esteem fare better than those with low self esteem. Additionally, students with high self esteem exhibit superior mathematical communication skills compared to students with low self esteem. Notably, an interaction between the learning model and self esteem was observed, influencing mathematical communication skills.